Epic Stone Butch transmasculinity in the work of Willa Cather - Hammer, K. Allison (Transgender Studies Quarterly, 2020)
Through application of the contemporary term transmasculinity and the more historical stone butch, the author questions the critical tendency to perceive American writer Willa Cather only as lesbian while ignoring or undertheorizing a transgender longing at play in her fiction, short stories, and letters. While biographical evidence must not be approached as simply coterminous with literary production, as literature often exceeds or resists such alignments, Cather's letters in particular suggest a strong identification with her male fictional alliances. Analysis of her letters alongside two of her most treasured, and disparaged, novels, One of Ours (1922) and The Professor's House (1925), conveys Cather's wish for an idealized masculinity, both for herself and for Western culture, that would survive two coeval historical processes and events: the closing of the American frontier and the First World War. Through what the author calls a stone butch “armature,” she and her characters retained masculine dignity despite historical foreclosure of Cather's manly ideal, Winston Churchill's Great Man, who was for her the artistic and intellectual casualty of the period. Cather expressed the peculiar nostalgic longing present in stone butch, and in the explosion of new forms of transmasculinity in the present. This suggests that historical transgender styles don't disappear entirely, even as new categories emerge.
Keywords: 1900-1999; 1910-1919; 1920-1929; amériques; approches et analyses; arts; butch; discipline; identités LGBTQIA2+; personnes trans*; périodes historiques; queer; régions géographiques; états-unis; études littéraires

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Cet article porte sur les rôles que les femmes ont joué dans le développement d’une scène jazz à Montréal. Les archives témoignent de l’importance des pianistes Vera Guilaroff et Ilene Bourne, de l’enseignante de piano Daisy Peterson Sweeney, des enseignantes de danse Olga Spencer Foderingham et Ethel Bruneau, ainsi que des danseuses de variétés dans le développement de la plus grande scène jazz du Canada au cours de la première moitié du xxe siècle. Cet article contextualise la présence des femmes dans ces espaces performantiels précis (le piano, l’enseignement, la danse) et explore les processus historiographiques liés à leur exclusion des récits historiques.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; DIG; amérique du nord; amériques; arts; canada; discipline; femmes* artistes; histoire; histoire et politique; historiographie; montréal; musique; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail

Femmes, attitudes performatives: aux lisières de la performance et de la danse - Colloque "Femmes, attitudes performatives, aux lisières de la performance et de la danse" (2012 : Vandœuvre-lès-Nancy, France); Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy (Collection Nouvelles scènes, 2014)
La place et le rôle des femmes dans l'art et dans le spectacle vivant, entre 1912 et 2012, aux lisières de la performance et de la danse. A l'heure des re-enactements et autres remakes des performances historiques, il semblait important de s'interroger sur la place des femmes dans les avant-gardes des années 1910-1970. Quel regard portons-nous, aujourd'hui, sur les pionnières qui ont profondément modifié la danse et la performance, en Europe et aux Etats-Unis ? Réunis pour la première fois, des historiens, des philosophes, des danseurs et deux chorégraphes ont accepté de faire le point sur leurs recherches. Par-delà les catégories artistiques (danse, performance, action, pantomime, théâtre, music-hall...) et les clivages (théorie / pratique ; forme / fond), ce livre est une invitation à partager leurs questionnements sur le spectacle vivant « au féminin », ses archives et ses références. Femmes, attitudes performatives rassemble dix contributions, une « interview performative » de La Ribot et un entretien sur La Part du rite de Latifa Laâbissi et Isabelle Launay.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artistes féministes; arts; corps; cours; danse; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire de la danse; performance; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

Radclyffe Hall: A life in the writing - Dellamora, Richard (Haney Foundation series, 2011)
The Well of Loneliness is probably the most famous lesbian novel ever written, and certainly the most widely read. It contains no explicit sex scenes, yet in 1928, the year in which the novel was published, it was deemed obscene in a British court of law for its defense of sexual inversion and was forbidden for sale or import into England. Its author, Radclyffe Hall, was already well-known as a writer and West End celebrity, but the fame and notoriety of that one book has all but eclipsed a literary output of some half-dozen other novels and several volumes of poetry. In Radclyffe Hall: A Life in the Writing Richard Dellamora offers the first full look at the entire range of Hall's published and unpublished works of fiction, poetry, and autobiography and reads through them to demonstrate how she continually played with the details of her own life to help fashion her own identity as well as to bring into existence a public lesbian culture. Along the way, Dellamora revises many of the truisms about Hall that had their origins in the memoirs of her long-term partner, Una Troubridge, and that have found an afterlife in the writings of Hall's biographers. In detailing Hall's explorations of the self, Dellamora is the first seriously to consider their contexts in Freudian psychoanalysis as understood in England in the 1920s. As important, he uncovers Hall's involvement with other modes of speculative psychology, including Spiritualism, Theosophy, and an eclectic brand of Christian and Buddhist mysticism. Dellamora's Hall is a woman of complex accommodations, able to reconcile her marriage to Troubridge with her passionate affairs with other women, and her experimental approach to gender and sexuality with her conservative politics and Catholicism. She is, above all, a thinker continually inventive about the connections between selfhood and desire, a figure who has much to contribute to our own efforts to understand transgendered and transsexual existence today.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; discipline; europe; histoire et politique; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; royaume-uni; régions géographiques; thématiques; études littéraires

Women in Dada: essays on sex, gender, and identity - Sawelson-Gorse, Naomi (The MIT Press, 2001)
Finally, a look at the role of women in the shaping of the high-spirited—but hardly feminist—Dada monement. For all of its iconoclasm, the Dada spirit was not without repression, and the Dada movement was not without misogynist tendencies. Indeed, the word Dada evokes the idea of the male—both as father and as domineering authority. Thus female colleagues were to be seen not heard, nurturers not usurpers, pleasant not disruptive.This book is the first to make the case that women's changing role in European and American society was critical to Dada. Debates about birth control and suffrage, a declining male population and expanding female workforce, the emergence of the New Woman, and Freudianism were among the forces that contributed to the Dadaist enterprise. Among the female dadaists discussed are the German émigré Baroness Elsa von Freytag-Loringhoven; Berlin dadaist Hannah Höch; French dadaists Juliette Roche and Suzanne Duchamp; Zurich dadaists Sophie Taeuber and Emmy Hennings; expatriate poet and artist Mina Loy; the "Queen of Greenwich Village," Clara Tice; Margaret Anderson and Jane Heap, the lesbian couple who ran The Little Review; and Beatrice Wood, who died in 1998 at the age of 105. The book also addresses issues of colonialist racism, cross-dressing and dandyism, and the gendering of the machine. The bibliography was compiled by the International Dada Archive (Timothy Shipe and Rudolf E. Kuenzli). Contributors Eleanor S. Apter, Barbara J. Bloemink, Willard Bohn, Carolyn Burke, William A. Camfield, Whitney Chadwick, Dorothea Dietrich, Susan Fillin-Yeh, Paul B. Franklin, Renée Riese Hubert, Marisa Januzzi, Amelia Jones, Marie T. Keller, Rudolf E. Kuenzli, Maud Lavin, Margaret A. Morgan, Dickran Tashjian, Elizabeth Hutton Turner, Barbara Zabel
Keywords: 1900-1999; 1910-1919; allemagne; amériques; approches et analyses; arts; cours; discipline; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; régions géographiques; sexisme; suisse; systèmes d'oppressions; thématiques; états-unis

Amazons of the avant-garde: Alexandra Exter ... [et al.] - Bowlt, John E.; Drutt, Matthew; Deutsche Guggenheim Berlin.; Bowlt, John E.; Drutt, Matthew; Deutsche Guggenheim Berlin. (Solomon R. Guggenheim Museum, 2000)
Amazons of the Avant-Garde presents work by six Russian women who contributed to the development of modern art in the first quarter of the 20th century: Alexandra Exter, Natalia Goncharova, Liubov Popova, Olga Rozanova, Varvara Stepanova, and Nadezhda Udaltsova. The catalogue includes several essays that discuss the hindrances and influences affecting women in Russian avant-garde art circles. In addition, each artist featured in the exhibition is individually discussed at length, along with biographical timelines and excerpts of their writings from letters and publications. Color reproductions of the works in the exhibition accompany the essays to form a cohesive illustration of the art world in Russia during the first decades of the 20th century and the women who changed the aesthetic canons of their time. Alexandra Exter -- Natalia Goncharova -- Liubov Popova -- Olga Rozanova -- Varvara Stepanova -- Nadezhda Udaltsova
Keywords: 1900-1999; 1910-1919; 1920-1929; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; russie; régions géographiques; thématiques